(untitled) (Patan Prospective Journal, 2025)
This study attempts to examine the influence of key bank specific factors namely capital adequacy ratio (CAR), non-performing loans (NPL), management efficiency, bank size, and growth rate—on the financial performance of commercial banks in Nepal. Financial performance is measured using two widely recognized indicators: return on assets (ROA) and return on equity (ROE). Utilizing a balanced panel dataset of 12 commercial banks over the period 2016/17 to 2023/24, the analysis encompasses 96 observations. This study employs descriptive statistics, correlation analysis, and multiple regression models to assess the relationships between the selected variables and financial performance. The results indicate that non-performing loans and bank size exert a statistically significant negative impact on ROA, suggesting that higher loan defaults and larger scale operations may undermine asset profitability. In contrast, management efficiency demonstrates a significant positive effect on ROA, highlighting the importance of effective operational management. Surprisingly, capital adequacy ratio (CAR) is found to have no significant association with ROA, challenging conventional assumptions about its role in profitability. The study concludes that NPL levels and management efficiency are critical determinants of financial performance in Nepal’s commercial banking sector, while increased bank size may contribute to inefficiencies rather than economies of scale. These insights carry important implications for banking regulators, policymakers, and institutional managers seeking to strengthen the financial health and sustainability of banks in Nepal. For future research, the study recommends incorporating primary data, alternative performance metrics, and macroeconomic variables to provide a more comprehensive understanding of bank performance dynamics.